Adipocyte-derived factors induce adherent to suspension transition in breast and pancreatic cancer cells through lipid metabolic alteration - Doru Kwon; Hyun Woo Park; Byung Soh Min; Junjeong Choi (Scientific Reports)
Abstract Adipocytes play a dynamic role in the tumor microenvironment (TME) by acting as facilitators, providing cytokines and metabolites that regulate cancer progression and metastasis. Despite metastasis being a major contributor to cancer-associated mortality, our understanding of how adipocytes influence this process remains limited. This study aims to elucidate the regulatory mechanism of Adherent to Suspension Transition (AST) reprogramming within the adipocyte, driven by anchorage dependency. AST facilitates the conversion of adherent tumor cells into suspension cells, thereby contributing to the generation of circulating tumor cells (CTCs). We have evaluated generating AST cells from primary tumors using a dissemination assay that mimics CTCs in vitro. Additionally, we examined AST cell formation when incubated with human adipocyte-conditioned media (ADCM) using the InCucyte live-cell imaging system. Through this approach, we effectively assessed the impact of the tumor-adipocyte interactions on CTC formation from the perspective of AST. As a metastasis-initiating marker, CD36 is pivotal in fatty acid (FA) acquisition and regulates lipid metabolic remodeling during the AST. The generation of AST cells through AST reprogramming is controlled by fatty acid oxidation (FAO), and pharmacological blockade of CD36 and FAO significantly reduced AST cell generation. This demonstrates that CD36 plays a key role in the early stages of AST-induced dissemination. Additionally, promoting cancer cell aggressiveness through ADCM enhances metastatic potency and upregulates the expression of AST reprogramming factors. Inhibition of lipid metabolism not only suppresses AST cell formation but also decreases survival in suspension. This indicates that exogenous lipid uptake and FAO via CD36 play crucial roles in the metastasis process, facilitating the dissemination of primary tumors into the bloodstream. Adipocytes contribute to cancer progression by supplying various metabolites to cancer cells. While primary tumors predominantly rely on glucose as a major energy source, cellular remodeling during dissemination shifts metabolic dependency toward lipids. In the TME, where adipocytes are abundant, tumor cells acquire FA through CD36-mediated uptake for metabolic adaptation. This shift to lipid metabolism is essential for AST, and thus, targeting lipid metabolism via inhibition of CD36 and FAO could serve as a potential therapeutic strategy for AST.